2014
DOI: 10.1186/1748-7161-9-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of coronal shift as an indicator of neuroaxial abnormalities in adolescent idiopathic scoliosis: a prospective study

Abstract: BackgroundIn previous studies, many indicator factors have been proposed to select patients who need an MRI screening of the spinal canal. In current study, the clinical and radiologic factors including coronal parameters of the curve were evaluated to find out which indicator is more important.MethodsA prospective study included 143 consecutive patients with the diagnosis of adolescent idiopathic scoliosis who were treated between 2010 and 2013 at our spinal clinics. Only patients with normal or subtle neurol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Zhang et al [10] considered that aged less than 10 years, being male or having left thoracic or right lumbar curve are risk factor. Beyond that long curve span, apex at thoracolumbar spine and hyperthoracic kyphosis and so on are also risk factor [3,[6][7][8][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. This study includes the second largest research sample to date.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [10] considered that aged less than 10 years, being male or having left thoracic or right lumbar curve are risk factor. Beyond that long curve span, apex at thoracolumbar spine and hyperthoracic kyphosis and so on are also risk factor [3,[6][7][8][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. This study includes the second largest research sample to date.…”
Section: Discussionmentioning
confidence: 99%
“…There are not many relevant studies searched on pubmed. Choon et al 9 suggested that males and patients with increased thoracic kyphosis are risk factor.Zhang et al 10 considered that aged less than curve span, apex at thoracolumbar spine and hyperthoracic kyphosis and so on are also risk factor 3,[6][7][8][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] .This study includes the second largest research sample to date. The risk factors identified in this study can be divided into three categories, namely, general, imaging, and neurologic characteristics; a total of 12 clinical indicators were included in the correlation analysis.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies and this study, the incidence of intramedullary abnormalities in patients initially diagnosed with idiopathic scoliosis is approximately 6.3% to 9.9% 4 There are not many relevant studies searched on pubmed. Choon et al 9 suggested that males and patients with increased thoracic kyphosis are risk factor.Zhang et al 10 considered that aged less than 10 years, being male or having left thoracic or right lumbar curve are risk factor.Beyond that long curve span, apex at thoracolumbar spine and hyperthoracic kyphosis and so on are also risk factor 3,[6][7][8][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] .This study includes the second largest research sample to date. The risk factors identified in this study can be divided into three categories, namely, general, imaging, and neurologic characteristics; a total of 12 clinical indicators were included in the correlation analysis.…”
Section: Discussionmentioning
confidence: 99%